Biofeedback y entrenamiento muscular del piso pélvico en la rehabilitación de la incontinencia fecal - Berna B., Lorena; Weisser P., M. Teresa; Arancibia L., Angélica (Revista Hospital Clínico Universidad de Chile, 2010)
Objective: To evaluate biofeedback plus Pelvic Floor Muscle Training (PFMT) on Fecal Incontinence (FI) treatment included at Physical and Rehabilitation Medicine Service. Method: Prospective cohort. Patients who had FI and met the inclusion criteria were engaged in45-minute biofeedback and PFMT, three times per week, for ten sessions. Demographycal and clinical data were registered. Outcomes were quantified by the Vaizey (modified Wexner) Fecal Incontinence Severity score and Fecal Incontinence Quality of Life (FIQL), measured before and after intervention. Results: A total of seventeen patients completed treatment during January2007 to December 2008. Fifteen of those were female. Mean age (SD) was 64.7 (9.61), range 51 – 88. Eight patients (47%) had some known risk factor associated to FI. Mean baseline Vaizey score was 13.11 (CI 95% 9.88 – 16.35). Lower scores on FIQL domains were depression and embarrassment. After Pelvic-Floor Rehabilitation, Vaizey score improvement was statistically significative (6.94, CI 95% 4.13 – 9.75, p < 0.001), and FIQL as well (p< 0.05). Discussion: biofeedback plus PFMT is a therapeutical approach in Mild-to-moderate Fecal Incontinence, but we observed good response even in severe cases. Outcomes such Fecal Incontinence Severity and QoL had both statistical and clinical significance. Conclusions: In patients with Fecal Incontinence, our experience with biofeedback and PFMT as a Rehabilitation Programme provided outcomes which were clinically and statistically significant and proved to be a reliabletherapeutical alternative for this kind of condition, independent of its severity.